The consequences of Germany’s scorched-earth policy for the inhabitants of the Vištytis area during World War II - Ražinskaitė, Ugnė (Genocidas ir rezistencija, 2013)
Based on the story of one family, the article discusses the experience of the inhabitants of the Vištytis area (now the village of Totorkiemis, Vilkaviškis district) in the aftermath of the Nazi scorched-earth policy at the end of the Second World War. It examines the relations of the evacuees with civilian and military Germans and Soviets, as well as with Poles. It focuses on the family’s home life and the war experience in exile.
Keywords: German occupation; second world war; economy; deportations; polish